Impact of COVID-19 on the Performance and Stability of Conventional and Islamic Banks in the GCC Region, Malaysia, and Pakistan - Qazi Yasir Arafat; Abdul Rashid; Qazi Waseem Jan (Islamic Banking and Finance Review, 2021)
This study examines the impact of COVID-19 on the performance and stability of conventional and Islamic banks. The sample included all the 21 listed Islamic banks (IBs) and 44 listed conventional banks (CBs) from the GCC region, Malaysia, and Pakistan. Quarterly data of these banks covering the period January 2019 to June 2020 were obtained from their quarterly reports. Performance was measured by return on assets (ROA) and return on equity (ROE), while stability was measured by the Z-scores of these banks. Based on the previous literature, a better performance of IBs was expected because these banks are based on the participatory mode of financing instead of debt-based financing. However, the results of the current study showed a significant and negative impact of COVID-19 on the financial performance of both types of banks, suggesting that either type of banking was significantly affected during the pandemic. However, we did not find any significant evidence of the impact of COVID-19 on the stability of these banks.